Residential sources of pesticide exposure during pregnancy and the risks of hypospadias and cryptorchidism: the French ELFE birth cohort. Issue 9 (14th August 2019) - Cognez, Noriane; Warembourg, Charline; Zaros, Cécile; Metten, Marie-Astrid; Bouvier, Ghislaine; Garlantézec, Ronan; Charles, Marie-Aline; Béranger, Rémi; Chevrier, Cécile
Abstract : Objectives: Prenatal occupational exposure to pesticides has been associated with male reproductive tract abnormalities. Little is known about the possible impact of non-occupational pesticide exposure on fetal and child development in the general population. Using data from a nationwide birth cohort, we aimed to assess the association between residential sources of prenatal pesticide exposure and the risks of hypospadias and cryptorchidism. Methods: Of the 9281 boys in ELFE (French Longitudinal Study of Children), the national French birth cohort, 53 were diagnosed with hypospadias and 137 with cryptorchidism. We assessed residential exposure sources from self-reported domestic use of eight types of pesticide products and French spatial land use data with acreage within a 1000 m radius around each family's home for 21 crop types. We used logistic regression modelling, adjusted for possible confounders that included estimated dietary pesticide intake. Multiple imputations were used to handle missing data. Results: An increased risk of hypospadias was associated with domestic pesticide use against fleas and ticks (OR=2.28, 95% CI 1.09 to 4.75); no associations were found between cryptorchidism and any domestic pesticide use. Slightly increased risks of cryptorchidism were observed in association with all crop acreages near homes during pregnancy, especially for orchards, and no association was observed for hypospadias. Conclusions: Our results suggest a possible increased risk of hypospadias associated with prenatal use of some domestic pesticide products, likely to contain insecticides, and of cryptorchidism with nearby orchard acreage (crops repeatedly sprayed with pesticides). This work is limited by its modest number of cases.